Potential Application of Chimeric Antigen Receptor (CAR)-T Cell Therapy in Renal Cell Tumors - Schepisi, Giuseppe; Conteduca, Vincenza; Casadei, Chiara; Gurioli, Giorgia; Rossi, Lorena; Gallà, Valentina; Cursano, Maria Concetta; Brighi, Nicole; Lolli, Cristian; Menna, Cecilia; Farolfi, Alberto; Burgio, Salvatore Luca; et al. (Frontiers in Oncology, 2020)
Currently, renal cell carcinoma is characterized by encouraging benefits from immunotherapy that have led to significant results in treatment outcome. The approval of nivolumab primarily as second-line monotherapy and, more recently, the approval of new combination therapies as first-line treatment have confirmed the importance of immunotherapy in this type of tumor. In this context, the chimeric antigen receptor (CAR)-T represents a further step forward in the field of immunotherapy. Initially tested on hematological malignancies, this new therapeutic approach is also becoming a topic of great interest for solid tumors. Although the treatment has several advantages over previous T-cell receptor-dependent immunotherapy, it is facing some obstacles in solid tumors such as a hostile tumor microenvironment and on-tumor/off-tumor toxicities. Several strategies are under investigation to overcome these problems, but the approval of CAR-T cell therapy is still some way off. In renal cancer, the significant advantages obtained from immune checkpoint inhibitors represent a good starting point, but the potential nephrological toxicity of CAR-T cell therapy represents an important risk. In this review, we provide the rationale and preliminary results of CAR-T cell therapy in renal cell malignancies.